The Application of Talaqqi Method in Learning Tajweed and Fasahah Before Memorizing the Qur'an for Students at Darul Hikmah Islamic Boarding School in Luwuk, Banggai Regency, Central Sulawesi. - Salere, Ahmad Algifari; Munir, Munir; Salahuddin, Salahuddin (Jurnal Mercusuar, 2021)
This research aims to 1) determine the implementation of the talaqqi method in improving tajwid and fasahah in the learning process of the Qur'an for students at Pondok Pesantren Daarul Hikmah Luwuk, Banggai Regency. 2) Identify the factors that hinder and support the implementation of the talaqqi method in improving tajwid and fasahah in the learning process of the Qur'an for students at Pondok Pesantren Daarul Hikmah Luwuk, Banggai Regency. 3) Find out the solutions taken by the mentors to overcome obstacles to the talaqqi method in teaching tajwid and fasahah at Pondok Pesantren Daarul Hikmah Luwuk, Banggai Regency. The research is a qualitative descriptive type with a case study approach, and the key instruments used are interviews, observations, and documentation. The results show that the implementation of the talaqqi method in improving tajwid and fasahah in the learning process of the Qur'an for students at Pondok Pesantren Daarul Hikmah Luwuk, Banggai Regency involves the teacher reading the surah to be learned or memorized, and then the students imitating it. The factors hindering the students from improving their tajwid and fasahah before memorizing the Qur'an include requiring a long time, the students' dialect, laziness, and previous preparation by their parents. On the other hand, the factors supporting the students in the learning process include adequate facilities, skilled teachers, supportive environment, easy-to-understand methods, and thorough learning. The solutions taken by the mentors to overcome obstacles to the talaqqi method in teaching tajwid and fasahah at Pondok Pesantren Daarul Hikmah Luwuk, Banggai Regency include providing a guidebook, having proficient students help their peers, giving motivation, prohibiting the use of mobile phones, and applying punishment for violating the pesantren rules. The implication of this research is that with professional teachers in their respective fields, committed students following the learning program with the appropriate methods and adequate facilities, the learning objectives can be achieved.